Self-Assembly of 3D Fennel-Like Co3O4 with Thirty-Six Surfaces for High Performance Supercapacitor. (7th March 2017) - Li, Yanfang; Hai, Zhenyin; Hou, Xiaojuan; Xu, Hongyan; Zhang, Zengxing; Cui, Danfeng; Xue, Chenyang; Zhang, Binzhen
Abstract : Three-dimensional (3D) fennel-like cobalt oxide (II, III) (Co3 O4 ) particles with thirty-six surfaces on nickel foams were prepared via a simple hydrothermal synthesis method and its growth process was also researched. The crystalline structure and morphology were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), and Raman spectroscopy. The Brunauer-Emmett-Teller (BET) analysis revealed that 3D fennel-like Co3 O4 particles have high specific surface area. Therefore, the special structure with thirty-six surfaces indicates the good electrochemical performance of the micron-nanometer material as electrode material for supercapacitors. The cyclic voltammetry (CV), galvanostatic charge-discharge, and electrochemical impedance spectroscopy (EIS) were conducted to evaluate the electrochemical performances. Compared with other morphological materials of the similar sizes, the Co3 O4 particles on nickel foam exhibit a high specific capacitance of 384.375 F·g −1 at the current density of 3 A·g −1 and excellent cycling stability of a capacitance retention of 96.54% after 1500 galvanostatic charge-discharge cycles in 6 M potassium hydroxide (KOH) electrolyte.